Farmer business school. Learning manual for business skills: Manual for facilitators - Pham, Thi Mai Huong; Le, Thi Thanh Huong (Vietnam Women's Union, 2018)
This manual was produced as an initiative of the Towards More Profitable and Sustainable Vegetable Farming Systems in North-western Vietnam (AGB/2012/059) project by the ACIAR. The document provides Farmer Business School (FBS) facilitators with the tools, skills, and knowledge that will allow them to guide farmers as they go through their FBS experience. Through FBS, we hope for farmers to improve their business skills and obtain a better understanding of the different aspects relating to the agricultural product market through a learning-by-doing method. This manual is intended for and speaks to facilitators.